KOHERENSI ANTAR CERITA DALAM PENYUTRADARAAN DRAMA LEPAS SABTU SORE BERCERITA - Isnaadi, Muhammad Aldila; Setiawati, Sri Wastiwi (Seni Media Rekam ISI Surakarta, 2016)
Nowadays, Omnibus is the soap opera program which rarely appears on the televiseprogram in Indonesia. With soap opera program, there are so many short movies which arebroadcasted by televise stations. But, the story of short movies should be repackaged. Inaddition,duration of Soap Opera Sabtu Sore Bercerita is 48 including 3 stories of short movies.Adirector was covering three short movies through coherency to connect locations, an artist,and time.Keywords:Omnibus, coherency, soap opera,and Sabtu Sore Bercerita